Cvyaz indeksa napryazhennosti regulyatornykh sistem i drugikh pokazatelej serdechnogo ritma so spetsial'noj rabotosposobnost'yu lyzhnikov-gonshchikov - Bogatov, A. A. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The purpose of the research was studying of connection of individual values of an index of intensity in the different periods of the year training cycle with results of competitions of skiers. 35 men aged 17-18 years having 2-nd and 3-rd categories on ski races and engaged in one training group have taken part in the research. The average height was 174,33 ± 3,74 sm, weight - 66,6 ± 7,02 kg. The supervision was spent within one year during transitive (May), preparatory (October) and competitive (February) the periods of the year training cycle. The serviceability of athletes was estimated by results shown on city competitions - ski races on 10 and 5 kms. The correlation analysis was carried out with the help of the standard PC software. The individual values index of intensity of skiers during the year training cycle correlate with results of the competitive activity. The definition of the mathematical parameters of hearth rate allows to predict the result which the athlete can achieve at any stage of the year cycle.